Proteases and protease inhibitors in saliva of hard ticks: Biological role and pharmacological potential - Černý, Jiří; Arora, Gunjan (Advances in parasitology, 2024)
Hard ticks (family Ixodidae) are significant vectors of pathogens affecting humans and animals. This review explores the composition of tick saliva, focusing on proteases and protease inhibitors, their biological roles, and their potential in vaccines and therapies. Tick saliva contains various proteases, mostly metalloproteases, serpins, cystatins, and Kunitz-type inhibitors, which modulate host hemostatic, immune, and wound healing responses to facilitate blood feeding and pathogen transmission. Proteases inhibit blood clotting, degrade extracellular matrix components, and modulate immune responses. Serpins, cystatins, and Kunitz-type inhibitors further inhibit key proteases involved in coagulation and inflammation, making them promising candidates for anticoagulant, anti-inflammatory, and immunomodulatory therapies. Several tick proteases and protease inhibitors have shown potential as vaccine targets, reducing tick feeding success and pathogen transmission. Future research should focus on comprehensive proteomic and genomic analyses, detailed structural and functional studies, and vaccine trials. Advanced omics approaches and bioinformatics tools will be crucial in uncovering the complex interactions between ticks, hosts, and pathogens, improving tick control strategies and public health outcomes.
Keywords: Serpins; Tick-borne pathogens; Humans; Ixodidae; inhibitory proteas; Kunitz-type inhibitors; Peptide Hydrolases; Proteases; lidé; zvířata; Anticoagulant therapy; Saliva; Vaccine development; Protease inhibitors; sliny; Animals; Tick saliva; Immune modulation; Protease Inhibitors; proteasy; Cystatins